Development of A Four-Tier Diagnostic Test For Misconception of Oscillation and Waves - Ridho Adi Negoro; Viga Karina (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2019)
Difficulty understanding students' concepts needs to be known so that improvements can be made so that eventually students can master the concepts well. Misconception diagnostic tests can be an alternative to uncovering causes or factors of misconception in students. This study aims to develop a Four-Tier Test diagnostic test instrument to diagnose students' misconceptions on vibration and wave material to adapt the Mechanical Waves Conceptual Survey by Thongchai which has content compatibility with the segmentation of Indonesian curriculum material. This research is a development study using 3D development models. The 3D development model consists of 3 stages, namely: 1) Define, 2) Design and 3) Develop. The developed four-tier test diagnostic test instrument consists of 22 multiple-choice questions. The results of the content validation by three experts stated that the instrument was very feasible with an average percentage of 87%. Empirical trial results show as many as 22 valid diagnostic test items have enough to good power a level of difficulty and discrimination power. The reliability of the questions was analyzed using the Kuder Richardson formula of 0.765 with a high category. This instrument can be used to minimize the time spent in the process of identifying misconceptions because it is in the form of multiple-choice with varied questions.